1983
DOI: 10.1029/ja088ia01p00253
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamo simulation of ionospheric currents and their connection with the equatorial electrojet and counter electrojet: A case study

Abstract: The interrelationship of equatorial and planetary scale ionospheric horizontal currents on quiet days is studied by means of a global ionospheric wind dynamo simulation. This simulation aims at reproducing magnetic and radar data first for a normal quiet day, and then for the strong counterelectrojet event of January 21, 1977, which was previously studied in detail on the basis of coherent backscatter radar data for the Addis-Ababa location. For the reference quiet day (January 27, 1977), the pattern of low an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…It should be noted that the present analyses did not directly exhibit spatial variations of the current system, since the pre-sunset IEEJ and the PRE strength around sunset were obtained at the same longitude at different times. Several earlier models and observational studies have proposed that the evening CEJ is caused by semi-diurnal tides (e.g., Hanuise et al, 1983;Alex and Mukherjee, 2001;Gurubaran, 2002). The semi-diurnal tides are not likely to vary dramatically within a few hours or several tenths of longitudes.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the present analyses did not directly exhibit spatial variations of the current system, since the pre-sunset IEEJ and the PRE strength around sunset were obtained at the same longitude at different times. Several earlier models and observational studies have proposed that the evening CEJ is caused by semi-diurnal tides (e.g., Hanuise et al, 1983;Alex and Mukherjee, 2001;Gurubaran, 2002). The semi-diurnal tides are not likely to vary dramatically within a few hours or several tenths of longitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms have been suggested to explain CEJ. Modeling studies have shown that a particular combination of tidal modes can result in a counter electrojet (Forbes and Lindzen 1976b;Takeda and Maeda 1981;Hanuise et al 1983). The study performed by Raghavarao and Anandarao (1980) showed that an upward wind with a sufficiently large magnitude (15-20 m/s) can also cause a counter electrojet.…”
Section: Counter Electrojetmentioning
confidence: 99%
“…Later in the evening the normal EEJ conditions seems to be re-established and a weak scattering is observed between 101 and 109 km of altitude. The evidence of moderate magnetic disturbance shown by the D st index indicates that the disappearance of the irregularities around midday could be due to neutral wind circulations changes caused by the disturbance dynamo effect on the Sq system as stated by Hanuise et al (1983) and . Regarding the scattering region during CEJ event, the reversal into the Doppler velocities with respect to the normal condition indicates that both the polarizations electric field and the density gradient are downward.…”
Section: The Afternoon Cej Eventmentioning
confidence: 99%
“…The longitudinal coverage of such phenomena can not be specified in the present work, however. In order to confirm the combination of global scale tidal wind modes proposed by Hanuise et al (1983), instead of the vertical winds and gravity wave associated shearing winds proposed by Raghavarao and Anandarao (1987) we need simultaneous observations in different latitudinal sector based on clusters of instruments like those used in the present work. Moreover, checking which, among the three components, is the responsible for driving the EEJ electric field will demand accurate neutral atmosphere wind measurements.…”
Section: The Morning Cej Eventmentioning
confidence: 99%
See 1 more Smart Citation